The Effects of Tax Avoidance, Accrual Earnings Management, Real Earnings Management, and Capital Intensity on the Cost of Equity - Firmansyah, Amrie; Febriyanto, Ahmad Sigid (Jurnal Dinamika Akuntansi, 2018)
This study aims to examince the effects of tax avoidance, accrual earning management, real earnings management and capital intensity on the cost of equity. The population of this study is a manufacturing company listed on the Indonesia Stock Exchange which amounted to 146 companies. The sampling technique used was purposive sampling and resulted in 420 units of analysis. This type of research is quantitative causality by performing hypothesis testing analysis is done by using multiple linear regression model. The findings of this research are tax avoidance will add to the risks that must be borne by investors thus increasing uncertainty over their investment. Investors consider that accrual profit management actions are opportunistic as risk-taking actions as well as real profit management actions. While on Capital Intensity, investors assume the information on the company’s fixed assets is not useful in making investment decisions. The conclusions that can be taken are tax avoidance, accrual profit management, and earnings management real positive to the cost of equity. However, capital intensity has a negative effect.